Penerapan Saintifik Pada Pembelajaran Pendidikan Agama Islam (SD Islam Bina Insani Muslim Bekasi) - Mia Fitrah Elkarimah (SAP (Susunan Artikel Pendidikan), 2018)
This research aims to describe the application of curriculum k13, especially scientific steps on the PAI (Islamic Education) subject in Islamic Elementary School Bina Insani Muslim Jatimulya in South Tambun subdisstrict, Bekasi Regency. The research instruments consist of observation, interview and documentation. The data of the research are analyzed employing a qualitative descriptive technique. The result of the one-month research shows that the scientific steps have been implemented as a whole. However, its implementation is not in accordance with the regulations of Minister of Education and Culture of Republic of Indonesia, consisting of 5 steps: observing, asking, trying, reasoning or associating and communicating. The inadequacy of the scientific steps in PAI learning can be seen in its non-sequential implementation. In the observing step, the aspect of aqidah (faith) is a dominant obstacle because it contains the concept of knowledge that is related to a belief and its abstract character. The discussions in this step tend to be rowdy and not focused. Besides, the imitating activity is only applied to aspects of fiqih (jurisprudence), such as the material of cleaning procedure. In the associating step, especially on the aspects of Al-Qur'an and hadith, students find it difficult to associate the contents of Al-Qur'an with the phenomena in their daily life, especially for students who have just learned to read Al-Qur'an. The last one is communicating ideas has not organized yet and tends to be quiet.